PERANCANGAN DAN IMPLEMENTASI APLIKASI SISTEM INFORMASI DOKUMENTASI DAN PELAPORAN DOKUMEN BORANG AKREDITASI PROGRAM STUDI PADA UNIVERSITAS MEDAN AREA PROGRAM PKM DIYA 2019 - Juanda Hakim Lubis; Rizki Muliono; Nurul Khairina (STMIK KAPUTAMA, 2020)
Medan Area University (UMA) is one of the oldest private universities in northern Sumatra, which was founded by Haji Agus Salim Siregar in 1983. Especially at Medan Area University the document collection processing model for LKPS-APS is currently still not organized with neat and there is still a loss of LKPS-APS documents, especially when the deadline for LKPS-APS preparation is nearing the upload period. To improve performance in document processing, a system will be built to facilitate lecturers and staff in managing LKPS-APS documents properly and in detail, and reduce the reason lecturers or staff cannot attend meetings in the processing and collection of LKPS-APS document forms that can be submitted into the online system and online discussion per document in the LKPS-APS information system according to 9 standard criteria according to the Instrument Akreditasi Program Studi 4.0 (IAPS 4.0) for Study Program Accreditation.